Sex-specific Feeding Behavior of Adult House Flies, Musca domestica L. (Diptera: Muscidae). Issue 1 (28th October 2022) - Neupane, Saraswoti; Hall, Brandon; Brooke, Grant; Nayduch, Dana
Abstract: House flies, Musca domestica L., (Diptera: Muscidae) mechanically vector diverse disease-causing microorganisms while foraging for food in agricultural and urban habitats. Although flies are diverse feeders, nutrient composition of food is important for both fly longevity and reproduction, especially for anautogenous females who require protein for egg production. We investigated whether fly sex and/or mating status influenced their preference for foods with varying macronutrient composition. Presumably mated or unmated male and female flies were separated by sex and offered four food, each in 10% solution offered on cotton wicks: sugar (carbohydrate-rich), fat-free milk (protein-rich, moderate carbohydrate), egg-yolk (protein and lipid-rich), and water (no macronutrients). Foods were colored with nontoxic dyes, which were rotated between replicates. After 4h exposure, flies were dissected to determine the type of food(s) ingested. The interaction of house fly sex and food type significantly influenced food preference, where females preferred milk (protein and carbohydrate-rich food), and males preferred mainly sugar (carbohydrate-rich). Furthermore, 32.8% of females and 10.6% of males foraged on multiple foods. While interaction of sex and mating status had no effect on food preference, milk preference was significantly higher in presumably mated than unmated females. We also tested whether food color influenced fly feeding preference, and found that color was most significant when flies were offered one food type, but negligible when multiple food types were present. This study suggests that bait-based fly control strategies should consider sex-specific preferences for various food attractants if aiming to target and control both male and female house flies.